Toward net zero: an engine electrification strategy approach of fuel cell and steam injection - He, Zhengfei; Pontika, Evangelia; Laskaridis, Panagiotis (American Society of Mechanical Engineers (ASME), 2024)
The turbofan engine electrification is a promising element in the global effort to achieve the 2050 net-zero emission target. This transformative shift embraces alternative energy sources and amplifies system efficiency. Power injection, using the electric motor to provide power assistance for the gas turbine, is a promising concept. Batteries and fuel cells are emerging as prime candidates for replacing traditional fossil fuel power requirements, offering compelling advantages, particularly with electric powertrains offering superior efficiency compared to conventional gas turbines. This direct power injection assistance reduces the power requirement from the combustion, thus reducing the fuel flow and Turbine Entry Temperature (TET). As an outcome, this alteration yields favourable consequences, notably in the form of diminished Carbon Dioxide (CO2) and Nitrogen Oxide (NOx) emissions and lower engine fuel consumption. However, this transition comes at the cost of a potential thermal efficiency penalty, impacts engine stability, and adds extra weight. These drawbacks compromise the power injection’s benefit, highlighting the necessity for introducing electrification strategies in future engine designs. This paper presents an innovative electrification strategy using fuel cells as the power source for engine electrification. The strategy highlights the collection of water as a by-product, followed by treatment processes involving condensation, pressurisation, and superheating. In this configuration, the fuel cell is designed to provide power to the electric motor, which injects power into the low-pressure shaft of the engine and provides assistance. Additionally, steam injection, leveraging the by-product water, enhances the benefits derived from electrification by recovering and redirecting the waste heat from exhaust gases into the combustor. To evaluate the potential impact of this electrification strategy, this research selected and modelled three representative engines, each representative of typical thermodynamic cycles. Two different approaches to steam management were considered, including instantaneous injection with production and storage of steam during production for release during specific flight segments. This research established the synergy between steam injection and different engine thermodynamic cycles, providing a visualised evaluation method. The impact of fuel cell electrification on fuel consumption has been quantified. An estimation of the weight penalty, including fuel cells, hydrogen storage and heat exchanger, is also provided. Furthermore, the sizing of the superheating heat exchanger is analysed to assess its influence on the electrification strategy. This research discovered the impact of steam injection on different engine cycles, established the benefits and constraints, and explained the physics. This research has captured the physics of recovering the waste heat from exhaust pipes, which could compromise fuel consumption benefit and impose a penalty on electrification. This research also indicated under what conditions and phases it is better to use the fuel cell with steam injection. The results and assessments reach the conclusion that the electrification strategy of fuel cell and steam injection is preferable for high-temperature, low-specific thrust engines. An improper deployment could lead to a penalty instead of a benefit. The temperature of the steam is the dominant factor in bringing fuel consumption benefits. Thus, the preferable steam management approach is to inject during T/O and climb.
Keywords: 40 Engineering; 4010 Engineering Practice and Education; 7 Affordable and Clean Energy; 13 Climate Action